"Halfway Independent": Experiences of formerly homeless adults living in permanent supportive housing. Issue 3 (2nd October 2021) - Pilla, David; Park‐Taylor, Jennie
Abstract: Permanent supportive housing (PSH), which combines affordable public housing with social services, has become the dominant model in the United States for providing housing to formerly homeless people. PSH has been effective in reducing re‐entry to homelessness, yet has shown limited evidence of improving formerly homeless individuals' mental health and quality of life. This study aimed to understand the lived experiences of formerly homeless adults' adjustment to tenancy in PSH, with a focus on how living in PSH has affected their meaningful activity and social engagement. Based on a phenomenological approach, a thematic analysis was conducted using semi‐structured interviews with 17 individuals living in three PSH buildings in New York City. Results suggested that PSH was beneficial in fulfilling formerly homeless individual's basic needs and facilitating lifestyle improvements, yet many were dissatisfied with their living conditions and lacked meaningful activity, social integration, and community belongingness. These issues were found to develop in large part as a result of formerly homeless individuals' disharmonious relationships within the social context of PSH, consisting of staff members, other residents, and people in the surrounding community. The effects of the COVID‐19 pandemic and implications for PSH social services are discussed.